Aesthetic imagination and intuition - Domínguez Hernández, Javier (Estudios de Filosofía, 1992)
The article establishes a contrast between aesthetic intuition and imagination, as opposed to the illustrative and scientifical-objective version also assigned to these terms. The confusion between them has brought difficulties to Aesthetics and the Philosophy of Art. Adorno and Gadamer have once again brought these concepts to the foreground, laying special emphasis on their potential autonomy and interpretability, thereby renewing the relation between philosophical truth and the experience of art.